KESULITAN LITERASI NUMERASI DITINJAU DARI PEMECAHAN SISWA KELAS V - Anjar Agustina, Latifah; Danuri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Numeracy literacy is an important basic skill, but fifth-grade students at Jatimalang Public Elementary School still face difficulties, especially in solving story problems and contextual tasks. This study aims to describe the level of students' numeracy literacy in terms of the process of solving mathematical problems, identify difficulties at each stage of problem solving, and explore the factors that influence it. The research method used was descriptive qualitative. Data were collected through observation, problem-solving tests, interviews with the principal, classroom teachers, and several fifth-grade students. Data analysis was conducted inductively through the stages of reduction, presentation, and conclusion drawing. The results showed that students' numeracy literacy skills were in the adequate category. The main difficulties were found in the stages of understanding the problem, designing strategies, and rechecking. These obstacles were caused by internal factors, such as low self-confidence and anxiety about mathematics, as well as external factors, such as teacher-centered learning methods and a lack of practice with real-world problems.